Anesthesia Management of Cold Agglutinin Disease in a Pregnant Patient: A Case Report - Jibran Ikram; Chase Jackson; Sabry Ayad (Clinical Case Reports)
ABSTRACT Cold agglutinin disease (CAD), a rare autoimmune hemolytic anemia (AIHA), is characterized by hemolysis triggered by activation of the classical complement pathway. AIHA is estimated to affect one in 100,000 people in the general population; however, its incidence in pregnant women is unclear due to the scarcity of published studies. Here, we present the case of a 37‐year‐old female (G2P1102) who presented for a repeat Cesarean section. Her peripartum course was complicated by anemia (hemoglobin 7.9 g/dL, hematocrit 29.4%) attributed to cold agglutinin disease, necessitating the transfusion of 20 units of blood during this pregnancy. She had been receiving prednisone 10 mg daily for anemia. Cold temperatures can trigger the activation of cold‐reactive antibodies, leading to red blood cells agglutination (clumping together). Preventing hypothermia reduces the likelihood of cold‐induced hemolysis, which is the primary therapeutic strategy for cold agglutinin disease. Anesthetic management for the cesarean section was accomplished via spinal anesthesia, complemented by pain control through bilateral transversus abdominis plane (TAP) blocks. This multidisciplinary approach facilitated effective pain management while considering the patient's underlying condition.